2014
DOI: 10.1016/j.clim.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells of the gut: Relevance to immunity and pathology

Abstract: Plasmacytoid dendritic cells (pDCs) are bone marrow-derived immune cells with the ability to express copious amounts of type I and III interferon (IFN) and can differentiate into antigen-presenting dendritic cells as a result of stimulation by pathogen-derived nucleic acid. These powerful combined functionalities allow pDCs to bridge the innate and adaptive immune systems resulting in a concerted pathogen response. The contribution of pDCs to gastrointestinal immunity is only now being elucidated and is provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 148 publications
0
34
1
Order By: Relevance
“…In the steady-state conditions, pDCs in Spl and MLNs expressed Siglec-H, CD62L, CXCR3, and C-C chemokine receptor 2 (CCR2) as well as CCR9 and a4b7, which are known as gut-homing receptors 35 ( Figure 4f and Supplementary Figure S3). Oral administration of DSS reduced the expression of CXCR3 and CD62L on MLN pDCs, whereas the expression of other molecules did not change ( Figure 4f and Supplementary Figure S3).…”
Section: Pdcs Accelerate Dss-induced Colonic Inflammationmentioning
confidence: 99%
“…In the steady-state conditions, pDCs in Spl and MLNs expressed Siglec-H, CD62L, CXCR3, and C-C chemokine receptor 2 (CCR2) as well as CCR9 and a4b7, which are known as gut-homing receptors 35 ( Figure 4f and Supplementary Figure S3). Oral administration of DSS reduced the expression of CXCR3 and CD62L on MLN pDCs, whereas the expression of other molecules did not change ( Figure 4f and Supplementary Figure S3).…”
Section: Pdcs Accelerate Dss-induced Colonic Inflammationmentioning
confidence: 99%
“…Upregulation of type I interferon (IFN) is essential to restrain HIV replication, especially at the early stages of infection [6]. The activation of IFN α expression occurs primarily through the engagement of toll-like receptors (TLR) 7 and 9 by single stranded RNA or CpG DNA, respectively (reviewed by [7]). It has been demonstrated that single nucleotide polymorphisms (SNPs) in TLRs are associated with an increased susceptibility to infection [811] and are involved in different progressions of HIV/AIDS, although a consensus has not been reached.…”
Section: Introductionmentioning
confidence: 99%
“…They recognize microorganisms, distinguish among them, and are able to induce different responses even to closely related organisms. This ability to respond appropriately to different microbial products is particularly important in the gastrointestinal tract, where diverse microbial flora are located in close proximity to DC10.…”
mentioning
confidence: 99%